Effects of plastic film mulching on soil greenhouse gases (CO2, CH4 and N2O) concentration within soil profiles in maize fields on the Loess Plateau, China - Wei-ge NAN; Shan-chao YUE; Hai-zhou HUANG; Shi-qing LI; Yu-fang SHEN (Journal of Integrative Agriculture, 2016)
Abstract: To better understand the effects of plastic film mulching on soil greenhouse gases (GHGs) emissions, we compared seasonal and vertical variations of GHG concentrations at seven soil depths in maize (Zea mays L.) fields at Changwu station in Shaanxi, a semi-humid region, between 2012 and 2013. Gas samples were taken simultaneously every one week from non-mulched (BP) and plastic film-mulched (FM) field plots. The results showed that the concentration of GHGs varied distinctly at the soil-atmosphere interface and in the soil profile during the maize growing season (MS). Both carbon dioxide (CO2) and nitrous oxide (N2O) concentrations increased with increasement of soil depth, while the methane (CH4) concentrations decreased with increasement of soil depth. A strong seasonal variation pattern was found for CO2 and N2O concentrations, as compared to an inconspicuous seasonal variation of CH4 concentrations. The mean CO2 and N2O concentrations were higher, but the mean CH4 concentration in the soil profiles was lower in the FM plots than in the BP plots. The results of this study suggested that plastic film mulching significantly increased the potential emissions of CO2 and N2O from the soil, and promoted CH4 absorption by the soil, particularly during the MS.